Determination of mineral profiles in germinated legumes cowpea (Vigna unguiculata) and broad bean (Vicia faba) (Research, Society and Development, 2020)
The goal of this study was to assess the mineral profiles of cowpea (Vigna unguiculata) and broad bean (Vicia faba) during mature green (in natura), seed, and germination stages. Green beans and seeds were purchased, the later being germinated and immediately afterwards lyophilized and packaged. Analytes were determined using inductively coupled plasma optical emission spectroscopy (ICP-OES). Macro minerals K, P, and Mg exhibited the highest levels in legumes cowpea and broad bean. Among the micro minerals, Fe exhibited the highest amount in pigeon pea and lablab bean. There was a variation in mineral levels between the different stages of the beans, with a tendency to increase their concentrations after germination. No heavy metals were detected, with the exception of barium and strontium. The results indicated that the flours of cowpeas and broad beans, in general, met the National Health Surveillance Agency (ANVISA) recommendations for daily intake of macro and micro minerals. It is concluded that the flours of legumes in different stages can contribute as good sources of minerals to be included in individuals diets.